Optimization and characterization of Candida cylindracea lipase produced from palm kernel cake by solid-state bioconversion - Alam, Md. Zahangir; Elgharbawy, Amal Ahmed; Hamzah, Mohd. Salleh (2013)
The study aimed to produce lipase using abundant raw material in Malaysia employing a cost- effective method which is solid-state bioconversion (SSB). The optimization of the production was achieved with 400 U/gds which was more than 4-folds compared to the screening experiments. Characterization of the produced lipase showed promising results in terms of stability as well as in the hydrolysis of lipids. The enzyme was stable at 50-55°, contact time of one hour and hydrolyzed reaction to 50% free fatty acids.